Pengembangan Sistem Informasi JDIH Berbasis Web di Kabupaten Pesawaran - Agusto, Rio; Efendi, Dwi Marisa; Supriyanto, Supriyanto (Universitas Multi Data Palembang, 2025)
This research focuses on the development of a web-based Legal Documentation and Information Network System (JDIH) in Pesawaran Regency, integrated with the Legal Service System (SIPE Hukum). Using the Extreme Programming (XP) methodology, the system is developed iteratively to be more responsive to user needs. The technology utilized includes PHP and MySQL to enhance the efficiency of document management and legal information access for both the public and relevant institutions. The research findings indicate that the system can automate legal document management, accelerate information distribution, and improve transparency in legal services. In conclusion, the implementation of this system can optimize efficiency, accessibility, and accuracy in legal document management in Pesawaran Regency.